INFECTIVE ENDOCARDITIS AND MALIGNANT NEOPLASMS: FACTS AND HYPOTHESES - N. S. Chipigina; N. Yu. Karpova; V. А. Barsegyan; V. Т. Timofeev (Klinicist)
The problem of the association of infective endocarditis (IE) and oncological diseases has been discussed for more than 60 years, and is now becoming increasingly relevant because of observed increasing of number IE in elderly patients. The review of the literature presents both data on the incidence of oncological diseases diagnosed with IE and in the long-term follow-up of patients after IE, as well as current estimates of IE incidence in cancer patients, obtained in large population-based studies. The highest risk of IE development was found in patients with tumors of the colon and rectum, and the predominant etiological role of Streptococcus bovis/gallolyticus was proved in such cases. The frequency of concomitant oncological diseases is higher in elderly patients with IE. On the other hand, it is obvious that IE can be considered as a marker of latent oncological pathology, especially gastrointestinal tumors, malignant blood diseases and lymphoproliferative diseases that are most often detected during the period of active IE and in the first 1–2 years later. Therefore, mandatory colonoscopy is recommended for patients with IE caused by Streptococcus bovis/gallolyticus during the period of IE and annually in subsequent years, even if initially the colonoscopy did not reveal pathology. In elderly IE patients we should also be aware of the high likelihood of concomitant oncological pathology and carry out appropriate oncological search. Antimicrobial prophylaxis of IE in patients with gastrointestinal cancer remains unresolved.